2009
DOI: 10.1530/rep-08-0363
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular pH regulation in human Sertoli cells: role of membrane transporters

Abstract: Sertoli cells are responsible for regulating a wide range of processes that lead to the differentiation of male germ cells into spermatozoa. Intracellular pH (pHi) is an important parameter in cell physiology regulating namely cell metabolism and differentiation. However, pHi regulation mechanisms in Sertoli cells have not yet been systematically elucidated. In this work, pHi was determined in primary cultures of human Sertoli cells. Sertoli cells were exposed to weak acids, which caused a rapid acidification … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 53 publications
0
29
0
Order By: Relevance
“…Isolation of SC was made by a method described elsewhere (Oliveira et al 2009b) with some modifications. The tubules were centrifuged at 500 g for 5 min and washed in HBSSf followed by another centrifugation.…”
Section: Primary Sc Culturementioning
confidence: 99%
“…Isolation of SC was made by a method described elsewhere (Oliveira et al 2009b) with some modifications. The tubules were centrifuged at 500 g for 5 min and washed in HBSSf followed by another centrifugation.…”
Section: Primary Sc Culturementioning
confidence: 99%
“…In addition, the Sertoli cell number determines an upper limit for sperm production, a crucial detail (Sharpe, 1994(Sharpe, , 1999Buzzard et al, 2002). Sertoli cells facilitate the progression of degenerating germ cells and their remains (Griswold, 1995;Griswold, 1998;Buzzard et al, 2002;Mruk & Cheng, 2004;Oliveira et al, 2009) and it has been demonstrated that apoptotic spermatogenic cells and residual bodies are phagocytosed and degraded by Sertoli cells during mammalian spermatogenesis (Shiratsuchi et al, 1999;Xiong et al, 2008Xiong et al, , 2009.…”
Section: The Sertoli Cellmentioning
confidence: 99%
“…We can summarize these cell functions in two key aspects: formation of the seminiferous tubules and nutritional/structural/immunological support of the developing germ cells. Moreover, the SCs also control the ionic composition of the seminiferous epithelium [21] and the tubular fluid pH [22,23]. Fully differentiated SCs are often described as "nurse cells" and secrete several factors essential for spermatogenesis, including transferrin [24], glycoproteins [25], sulpho-proteins [26], myo-inositol [27], plasminogen activator [28] and androgen-binding protein [29].…”
Section: General Aspects Of Sertoli-germ Cell Associationmentioning
confidence: 99%